Penerapan Permainan Kokapal (Kosa Kata Kartu Palembang) Dalam Meningkatkan Minat Belajar Siswa di Kelas VI B Pada Pelajaran Baso Palembang - Astria, Rani (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to evaluate the effectiveness of implementing the Kokapal game (Palembang Vocabulary Cards) in increasing students’ learning interest in the Baso Palembang subject in Class VI B at SDN 021 Palembang. Students’ learning interest is a crucial aspect of the learning process, especially in local language education, which is often perceived as less engaging by students. Using a quasi-experimental approach, this research involves Class VI B students as research subjects, comparing their level of learning interest before and after the application of the Kokapal game. Data were collected through observations, learning interest questionnaires, and interviews with students and teachers to obtain a comprehensive understanding of students’ perceptions of the applied learning method. The results of the study indicate that the use of the Kokapal game significantly increases students’ learning interest, marked by enhanced active participation and enthusiasm in the learning process. The implications of this study suggest that game-based learning methods can be an effective alternative to increase students’ interest in Baso Palembang and have the potential to be applied to other subjects as well.